Engineering Strategies to Decode and Enhance the Genomes of Coral Symbionts - Levin, Rachel A.; Voolstra, Christian R.; Agrawal, Shobhit; Steinberg, Peter D.; Suggett, David J.; van Oppen, Madeleine J. H. (Frontiers in Microbiology, 2017)
Elevated sea surface temperatures from a severe and prolonged El Niño event (2014-2016) fueled by climate change have resulted in mass coral bleaching (loss of dinoflagellate photosymbionts, Symbiodinium spp., from coral tissues) and subsequent coral mortality, devastating reefs worldwide. Genetic variation within and between Symbiodinium species strongly influences the bleaching tolerance of corals, thus recent papers have called for genetic engineering of Symbiodinium to elucidate the genetic basis of bleaching-relevant Symbiodinium traits. However, while Symbiodinium has been intensively studied for over 50 years, genetic transformation of Symbiodinium has seen little success likely due to the large evolutionary divergence between Symbiodinium and other model eukaryotes rendering standard transformation systems incompatible. Here, we integrate the growing wealth of Symbiodinium next-generation sequencing (NGS) data to design tailored genetic engineering strategies. Specifically, we develop a testable expression construct model that incorporates endogenous Symbiodinium promoters, terminators, and genes of interest, as well as an internal ribosomal entry site from a Symbiodinium virus. Furthermore, we assess the potential for CRISPR/Cas9 genome editing through new analyses of the three Symbiodinium genomes. Finally, we discuss how genetic engineering could be applied to enhance the stress tolerance of Symbiodinium, and in turn, coral reefs.